The International Encyclopedia of Media Literacy 2019
DOI: 10.1002/9781118978238.ieml0214
|View full text |Cite
|
Sign up to set email alerts
|

Role of Entertainment Media in Sexual Socialization

Abstract: Entertainment media have become ubiquitous and influential in modern culture and serve as a sexual socialization agent for adolescents. Media messages often contain a large amount of sexual content and typically depict unhealthy, unrealistic, inaccurate, and incomplete information about sex and sexual health. Research has established a link between exposure to sexualized media content and gender‐stereotyped sexual beliefs, permissive sexual attitudes, and sexual behaviors. Studies have also found that consumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In this study, (as shown in Figure 1), 85 students obtained information about pubertal changes from friends, followed by books/magazines (81), schoolteachers (79), and movies (78). In contrast, lesser adolescents turned to their mother (16), father (17), and doctors (25) for information related to pubertal changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, (as shown in Figure 1), 85 students obtained information about pubertal changes from friends, followed by books/magazines (81), schoolteachers (79), and movies (78). In contrast, lesser adolescents turned to their mother (16), father (17), and doctors (25) for information related to pubertal changes.…”
Section: Resultsmentioning
confidence: 99%
“…(16) Further, television and the internet give fast access to sexual content, altering the adolescent perception of sexuality. (17) Smartphone provides various bene ts such as fast internet, video calling, easy access to social media, and gaming. (18) Increased smartphone use leads to addiction behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Latina/os typically have more restrictive attitudes about sex than non-Latina/os (Eisenman and Dantzker, 2006), which appear to differ across generational status depending on the specific sexual attitude in our study (see Table 1). Attitudes for Latina/o youth who are more exposed to US dominant cultural norms may be influenced more by the dominant culture than is the case for those with less 10.3389/fpsyg.2022.897311 exposure (Scull and Malik, 2019;Blanc, 2021), who may be more aligned to attitudes of their cultural heritage.…”
Section: Discussionmentioning
confidence: 99%
“…To uncover the essence of such processes, we should turn to the aesthetic and cinematic generalizations of a number of Western researchers (Freeman, 2015;Kawin, 2012;Lawrence, 2016;Och, 2015;Staiger, 2015;Scull & Malik, 2019), exploring various aspects of the functioning of artistic images of American horror films in modern popular culture. At the same time, the study of the ideology of discipline of educational spaces in cinema and, in particular, in the tradition of American horror films is still presented extremely fragmentary (Cole & Bradley, 2016;Walker, 2016).…”
mentioning
confidence: 99%